Accommodation, interpersonal justice, and the turnover intentions of employees with disabilities. Issue 1 (2nd January 2023) - Samosh, Daniel; Maerz, Addison; Spitzmuller, Matthias; Boehm, Stephan
Abstract: The number of employees with disabilities in the workforce is increasing and accommodations are essential to the work of many of these individuals. Prior research has explored perceptions of accommodation requests as well as coworkers' and managers' reactions to accommodations; yet, we know little about how employees with disabilities experience their own accommodations. We draw from the disability literature as well as contemporary justice and social exchange theory to develop and subsequently test a multilevel moderated mediation model on this subject. We test our hypotheses with data from 4, 083 employees nested in 256 workgroups across two time points. We find support for our prediction that accommodation-focused interpersonal justice influences turnover intentions. The effect of these justice perceptions was mediated by workgroup openness to communication. Further, we find that representation of accommodated employees with disabilities at the workgroup level plays an important role in these relationships. We look beyond the technical aspects of accommodation with this research to highlight the social experience of accommodation as a central driver of employee perceptions and work outcomes.